Molybdenum-99 (99Mo) Adsorption Profile of Zirconia-Based Materials for 99Mo/99mTc Generator Application - M Marlina; E. Lestari; A Abidin; H Hambali; I. Saptiama; S. Febriana; K Kadarisman; R. Awaludin; M. Tanase; K. Nishikata; K. Tsuchiya (PPIKSN-BATAN, 2020)
Technetium-99m (99mTc) plays a major role in diagnostic nuclear medicine and has not yet been replaced with any other radionuclides. It is available through the 99Mo/99mTc generator. The use of low-specific-activity 99Mo for 99Mo/99mTc generator application requires high adsorptive capacity sorbents. This study focused on the determination of 99Mo adsorption capacity of several zirconia materials, namely monoclinic nanozirconia, orthorhombic nanozirconia, sulfated zirconia, and phosphated zirconia. These materials were synthesized by using the sol-gel method and characterized using FT-IR spectroscopy, X-ray diffraction (XRD), and scanning electron microscopy/energy-dispersive X-ray spectroscopy (SEM-EDS). The determination of 99Mo adsorption capacity of these materials was carried out by soaking the materials in a Na299MoO4 solution with pH of 3 and 7, at temperatures ranging from room temperature to 90 °C, for 1 and 3 hours. The results indicated that monoclinic nanozirconia has a 99Mo adsorption capacity of 76.9 mg Mo/g, whereas orthorhombic nanozirconia, sulfated zirconia, and phosphated zirconia have 99Mo adsorption capacities of 150.1 mg Mo/g, 15.58 mg Mo/g, and 12.74 mg Mo/g, respectively. It appears that orthorhombic nanozirconia has the highest 99Mo adsorption capacity among the synthesized materials and can be applied as a candidate material for the 99Mo/99mTc generator.